China SL (sociedad líquida): cambio y polarización en la sociedad china contemporánea - Ollé, MANEL (Papeles del Este, 2007)
In this article are analyzed the Chinese society transformations that throughout the three last decades in relation to the conceptual frame of the passage of “solid or heavy modernity” to the “liquid or light modernity” that sociologist Zygmunt Bauman has theorized. The changes in the social stratification, the great internal migratory movements as well as the transformations in the communication of masses and the dominant ideology are analyzed here.